Sheep pestivirus in Morocco: sero‐epidemiological and molecular study. Issue 1 (3rd September 2019) - Fassi Fihri, Ouafaa; Jammar, Noâma; Amrani, Nadia; El Berbri, Ikhlass; Alali, Said
Abstract : The present study is the first to investigate Border disease caused by the sheep pestivirus (SPV) in sheep herds in Morocco. Sero‐epidemiological investigations were carried out in six regions of the Kingdom, known as important in terms of sheep breeding. A total of 760 blood samples were collected including aborted ewes from 28 randomly selected farms. The samples were analysed, for the determination of anti‐pestivirus antibodies, using indirect ELISA technique. Next, reverse transcriptase PCR (RT‐PCR) was conducted on serologically negative samples to identify possible persistently infected (PI) animals, through detection of specific RNA fragment. The results revealed an overall SPV seroprevalence in studied areas of 28.9%. The difference in seroprevalence between the six investigated regions was not statistically significant (p>0.05) and varied slightly from 20.9% to 37.5%. Furthermore, 93% of investigated farms were affected with an average seroprevalence of 22.7% (with a variation of 1%–74%). RT‐PCR results were all negative, indicating the absence of PI animals in the tested samples. Nevertheless, the present study revealed that SPV is endemic in Morocco.